Inappropriate Medication Use in Hospitalized Patients Diagnosed with Parkinson's Disease - Nicholas Cox; Jessica M. Louie; Benson H. Sederholm (MDPI AG, 2018)
The purpose of this study was to evaluate the rate at which potentially inappropriate medications were administered for patients diagnosed with Parkinson's disease (PD). This is a single-center, retrospective, case cohort study with data collected at an academic medical center between January 2010 and December 2013. Participants included all adult patients with admission diagnosis codes for PD. Included patients were screened for administrations of 27 potentially inappropriate medications and two potentially appropriate medications to be used for comparison. There were 1736 patients who met inclusion criteria with 175 documented administrations of potentially inappropriate medications to 77 patients. Patients who received potentially inappropriate medications had a longer mean duration of stay than the baseline population of PD patients (3.3 days vs. 1.9 days, p-value < 0.001). Despite recommendations to avoid certain medications in PD patients, a substantial number of administrations still occurred. The use of these medications can have clinical implications and our findings demonstrate increases in duration of stay. The findings from this study can assist in developing technological alerts to reduce inappropriate prescribing to PD patients. Larger prospective studies are warranted to further investigate the administration of inappropriate medications to patients diagnosed with PD.